Analysis of water reuse potential for irrigation in Lebanon - Eid-Sabbagh, K.; Roukoz, S.; Nassif, Marie-Helene; Velpuri, Naga Manohar; Mateo-Sagasta, Javier (International Water Management Institute, 2022)
Water scarcity and pollution are major threats for human development in the Middle East and North Africa (MENA) region, and Lebanon is no exception. Wastewater treatment and reuse in agriculture can contribute to addressing the increasing water crisis in the MENA region. However, what is the actual potential of water reuse as a solution for agriculture in Lebanon? This report addresses this question and provides the most comprehensive assessment of water reuse potential up to now. Using geographic information system (GIS) modelling and the best and most recent data available in the country, the report develops a detailed technical assessment of the quantities of treated water available for safe reuse in irrigation, and identifies the wastewater treatment plants that have the highest potential for that purpose. The report also examines the governance barriers that need to be overcome for the water reuse potential to materialize in practice. These barriers include structural shortcomings in the wastewater sector combined with challenges of governance and the lack of a regulatory framework for reuse management. Once the current economic, financial and political crisis in Lebanon eases, addressing these barriers will be key to achieving more and safer water reuse in the country.